Barriers to Learning Exposure In Construction 4.0: Perspectives From Built-Environment Students - Faremi, Olajide Julius; Arowolo, Habeeb Abiodun (UI Scholars Hub, 2025)
The ongoing digital transformation of the construction industry, known as Construction 4.0, requires students in built-environment programs to gain adequate exposure to emerging technologies. Despite this need, many faces significant barriers to meaningful engagement. This study explores the factors limiting students’ learning experiences related to Construction 4.0 in Nigerian universities and polytechnics. Using a stratified random sampling method, 154 students from one university and one polytechnic were surveyed through a structured questionnaire. Data were analyzed using frequency distribution, relative importance index, and the Mann-Whitney test. Results identify key obstacles such as limited peer collaboration, insufficient funding and resources, and weak infrastructure. There were no statistically significant differences in these barriers between university and polytechnic respondents. The study concludes that addressing the current limitations requires institutional reforms, including infrastructure investment, curriculum development, faculty training, and support for student collaboration, particularly in polytechnic settings.